PELATIHAN MANAJEMEN KEUANGAN KELUARGA BAGI KELOMPOK DASAWISMA “LELY 1” RT.08 RW.05 KELURAHAN BANDUNGREJOSARI KOTA MALANG - Tri Yulistyawati Evelina; Rena Feri Wijayanti; Ahmad Fauzi; Farida Akbarina (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Dasawisma